2017
DOI: 10.18632/oncotarget.16387
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic roles of Notch receptor mRNA expression in human ovarian cancer

Abstract: Aberrant activation of Notch signaling pathway has been correlated with high grade ovarian carcinoma and carcinogenesis. However, the predictive and prognostic values of Notch signaling pathway in ovarian cancer patients remains unclear. We utilize “The Kaplan-Meier plotter” (KM plotter) background database to access the prognostic values including overall survival (OS), progression-free survival (PFS), as well as post-progression survival (PPS) of four Notch receptor mRNA expression in ovarian cancer patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 56 publications
2
27
0
Order By: Relevance
“…Although several studies reported that high Notch3 expression was associated with worse overall survival time, others had contradictory findings . Additionally, high Notch3 expression has been correlated with better overall survival for all patients with ovarian cancer except with those who had serous cancer .…”
Section: Ovarian Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…Although several studies reported that high Notch3 expression was associated with worse overall survival time, others had contradictory findings . Additionally, high Notch3 expression has been correlated with better overall survival for all patients with ovarian cancer except with those who had serous cancer .…”
Section: Ovarian Cancermentioning
confidence: 99%
“…Activation of Notch3 attenuates the apoptotic effect of carboplatin by inhibiting carboplatin‐induced extracellular signal‐regulated kinase (ERK) phosphorylation . Although several studies reported that high Notch3 expression was associated with worse overall survival time, others had contradictory findings . Additionally, high Notch3 expression has been correlated with better overall survival for all patients with ovarian cancer except with those who had serous cancer .…”
Section: Ovarian Cancermentioning
confidence: 99%
“…The high expression of Notch2 mRNA has been significantly associated with poor PFS for all ovarian cancer patients, especially in grade II ovarian cancer. Interestingly, in serous and endometrioid cancer patients high expression of this mRNA was not correlated to poor PFS and OS [ 64 ].…”
Section: Notch Receptors and Resistance To Chemotherapy In Ovarian Camentioning
confidence: 99%
“…Mutational loss of the PRC2 complex has been often found in T‑ALL [ 28 ] The presence of Notch1 mutations has been significantly correlated with prednisone response, favorable minimal residual disease (MRD) kinetics and improved long-term outcome in children with T‑ALL [ 29 ] Breast cancer In all, 80% of epithelial hyperplasias of usual type (HUTs), 67% of ductal carcinomas in situ (DCISs), 89% of invasive ductal carcinomas (IDCs) and 57% of invasive lobular carcinomas (ILCs) revealed high expression of Notch1 [ 39 ] Ectopic expression of the NICD1 in MCF-7 breast adenocarcinoma cell line has been associated with the reduction of E‑cadherin levels [ 41 ] In MDA-MB-231 cells an increased migratory and invasive ability has also been detected [ 41 ] Downregulation of Notch1 caused cell cycle arrest in the G0/G1 phase but promoted apoptosis under in vitro conditions [ 43 ] Notch1 signaling might promote breast cancer cell invasion due to the activation of NF-κB and its downstream target genes including MMP-2, MMP-9 and VEGF [ 43 ] Notch4 showed an ability to transform mammary epithelium in vitro and in vivo. Moreover, an activated form of this receptor slowed ductal growth and perturbed lobular outgrowth prior to tumor formation Ovarian cancer The active form of Notch1 (NICD1) was detected in ovarian cancer cell lines, ovarian cancer specimens and may lead to growth inhibition of ovarian cancer cells upon depletion of Notch1 by Notch1 siRNA [ 64 ] Downregulation of Notch1 inhibits cells growth, induces G1 cell cycle arrest and induces cell apoptosis in A2780 ovarian cancer cells High expression of Notch1 mRNA was not correlated to PFS for all ovarian cancer patients [ 64 ] Notch2 seems to be a tumour suppressor in ovarian carcinogenesis [ 64 ] The high expression of Notch2 mRNA has been significantly associated with poor PFS for all ovarian cancer patients, especially in grade II ovarian cancer [ 64 ] Interestingly, in serous and endometrioid cancer patients high expression of this mRNA was not correlated to poor PFS and OS [ 64 ] The high level of Notch3 accompanied by a positive correlation with the expression of JAG1 and JAG2 has been detected in serous ovarian carcinomas [ 51 ] Overexpression of Notch3 has been significantly correlated with advanced stage, lymph node metastasis, chemoresistance and poor OS [ 51 53 ] Ectopic expression of Notch3 following transduction with NICD3 in ovarian surface epithelium and low-grade serous ovarian cancer cells led to increased resistance to carboplatin in vitr...…”
Section: Notch Signaling and Other Solid Tumorsmentioning
confidence: 99%
“…For example, it has been reported that NOTCH3 participates in the pathogenesis of EOC recurrence through enhancing carboplatin resistance of cancer cells 15. A high NOTCH4 mRNA expression level was revealed to be significantly correlated with a favourable overall survival (OS) of EOC patients and thus was regarded as a prognostic factor 16. As the γ‐secretase inhibitors in the Notch signalling pathway, DAPT and MK‐0752 have been reported to be highly promising therapeutic drug targets for treatment of EOC patients 17, 18.…”
Section: Introductionmentioning
confidence: 99%